Zadovoljstvo starejših uporabnikov zdravstvene nege na domu - Železnik, Danica (Obzornik zdravstvene nege, 2014)
Introduction: The user satisfaction with the home nursing care serves as an indicator of a subjective evaluation of the quality of their treatment. The purpose of this contribution is to show the study of the satisfaction level of home nursing care users. Methods: A quantitative research approach was used in this study. The data were gathered with a survey that included 186 users of home nursing care in the Osijek municipality in Croatia. A structured questionnaire was formed for the purposes of the research. The data gathered were statistically analysed with the SPSS 9.0 software. Results: The most emphasised was the users' satisfaction with the respect of discretion and privacy during nursing care activities 133 (72.0 %). Participants were also satisfied with the nurses' kindness and professionalism during nursing care activities 131(70.0 %), while 40 (21.5 %) participants were discontented with the time they had been given for the communication with their nurse. Discussion and conclusion: The research shows that participants are satisfied with the majority of home care activities, which may imply that nurses have performed their duties properly or that users are apprehensive that their examination and treatment might be interrupted if they showed any discontent. Users with only 2 visitations per week were the least satisfied with their nurse's activities, because a nurse only performs prescribed activities, and there is usually not enough time for conversation. Results of this research can be used for further planning and reorganisation of home care and they may serve as a solid background for future studies.
Keywords: Croatia; domače okolje; elderly; home environment; Hrvaška; medicinske sestre; nurses; nursing care; starostniki; zdravstvena nega